2007
DOI: 10.1111/j.1525-1438.2007.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epithelial and stromal tumor components on FIGO stages III and IV ovarian carcinosarcomas treated with primary surgery and chemotherapy

Abstract: The aim of this study is to assess the effect of epithelial and stromal tumor components on survival outcomes in FIGO stage III or IV ovarian carcinosarcomas (OCS) treated with primary surgery and adjuvant chemotherapy at the Northern Gynaecological Oncology Centre (NGOC), Gateshead. Women were identified from the histopathology/NGOC databases. Age, FIGO stage, details of histology, treatment, and overall survival were recorded. Of 34 cases (1994-2006, all FIGO stages), 17 were treated with primary surgery fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
0
26
3
Order By: Relevance
“…It accounts for 1-3 % of ovarian malignancies The staging system for ovarian and primary peritoneal cancer is also used for staging of MMMTs [3]. The adverse prognostic factors as stated by various studies are advanced age and stage, suboptimal cytoreduction, stromal predominant tumors and tumors with serous epithelial component [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 1-3 % of ovarian malignancies The staging system for ovarian and primary peritoneal cancer is also used for staging of MMMTs [3]. The adverse prognostic factors as stated by various studies are advanced age and stage, suboptimal cytoreduction, stromal predominant tumors and tumors with serous epithelial component [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine carcinosarcoma patients with serous/clear cell component have poor prognosis. Athavale et al (10) reported serous element as a poor prognostic factor for OCS patients. George et al (11) reported that among the histological features of UCS, the epithelial tumor could influence the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 34 patients with OCS, the presence of N 25% sarcomatous component in the primary tumor was associated with worse survival. In addition, tumors with serous epithelial components adversely affected the survival compared with non-serous components [31].…”
Section: Prognostic Factorsmentioning
confidence: 99%